2011
DOI: 10.1111/j.1439-0310.2011.01986.x
|View full text |Cite
|
Sign up to set email alerts
|

White Flank Spots Signal Feeding Dominance in Female Diamond Firetails, Stagonopleura guttata

Abstract: Plumage colour can be used as an honest signal to convey health and status, which has traditionally been examined in the sexual selection context of choosy females and elaborate males. We use a model avian system to study the role of plumage coloration in a social context such as inter- and intrasexual competition over food resources. The diamond firetail (Stagonopleura guttata) is an endemic Australian finch: females have more white flank spots than males, and white spot number was correlated with cell-mediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 78 publications
3
53
3
Order By: Relevance
“…Research has provided compelling evidence that the female ornamental phenotype is not under strong constraint due to genetic correlation and that female ornamental traits can change independently of male phenotype [9,10]. Such changes in female ornamentation have been inferred from recent research demonstrating female-specific functions of ornamentation in communication [11,12] and from comparative studies which have shown that female ornamental phenotype is evolutionarily labile, either becoming more or less exaggerated when compared with male ornamentation [5,10,13 -16]. A notable example comes from Martin and Badyaev's work, indicating that females evolve drabber plumage when they are subject to greater nest predation [6].…”
Section: Introductionmentioning
confidence: 99%
“…Research has provided compelling evidence that the female ornamental phenotype is not under strong constraint due to genetic correlation and that female ornamental traits can change independently of male phenotype [9,10]. Such changes in female ornamentation have been inferred from recent research demonstrating female-specific functions of ornamentation in communication [11,12] and from comparative studies which have shown that female ornamental phenotype is evolutionarily labile, either becoming more or less exaggerated when compared with male ornamentation [5,10,13 -16]. A notable example comes from Martin and Badyaev's work, indicating that females evolve drabber plumage when they are subject to greater nest predation [6].…”
Section: Introductionmentioning
confidence: 99%
“…survival, offspring recruitment, attractiveness to males. Female expression of competitive traits may increase access to important resources in the non-breeding season [3], [79], [88], [92][96], which could strengthen the observed benefits of aggression. However, competitive traits can also have negative effects on survival [8], [14], [16].…”
Section: Discussionmentioning
confidence: 99%
“…social selection; West-Eberhard, 1979. Although much research has supported the role of signals of status among males (Griggio, Serra, Licheri, Monti, & Pilastro, 2007;Møller, 1987;Pryke & Andersson, 2003;Senar & Camerino, 1998), few examples of status signalling in females have been described (but see Coady & Dawson, 2013;Crowhurst, Zanollo, Griggio, Robertson, & Kleindorfer, 2012;Crowley & Magrath, 2004;Murphy, Hernández-Muciño, Osorio-Beristain, Montgomerie, & Omland, 2009;Murphy, Rosenthal, Montgomerie, & Tarvin, 2009;Swaddle & Witter, 1995). This male bias in research results is surprising given that both males and females of many species compete for access to mates or other resources (Tobias et al, 2012).…”
Section: Authorsmentioning
confidence: 74%